Penerapan Ajaran Tri Nga dan Pertimbangan Pasar Kerja pada Minat Berkarir di Bidang Perpajakan - Dewi Kusuma Wardani; Sinta Devi (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this study was to determine the effect of the application of Tri Nga's teachings and labor market considerations on interest in a career in the field of taxation by using quantitative methods. Data collection uses primary data by distributing questionnaires to accounting students at Sarjanwiyata Tamansiswa University, Yogyakarta. Sampling method using convenience sampling. Data collection is carried out by distributing the Google Form link through the WhatsApp application. Data processed by 100 respondents. The results of this study indicate that the application of Tri Nga's teachings has a positive effect on interest in taxation careers, while labor market considerations do not affect interest in taxation career.